Gene Flow and Vertical Stratification of Pollination in the Bat‐Pollinated Liana Marcgravia longifolia - Malika Gottstein; Sarina Thiel; Jan Lukas Vornhagen; Christina Mengel; Marco Tschapka; Eckhard W. Heymann; Katrin Heer (Ecology and Evolution)
ABSTRACT Pollen dispersal is a key driver of gene flow in plant populations, shaping their spatial genetic structure (SGS). In tropical forests, plant‐pollinator interactions vary across vertical strata due to differences in microclimate, resource availability, and foraging behavior. Bats are an important tropical pollinator group and have been observed to exhibit vertical stratification in their foraging activity, with interaction frequencies differing across forest layers. They are highly mobile and expected to transport pollen over long distances; however, their actual contribution to gene flow has rarely been investigated. Marcgravia longifolia, a bat‐pollinated Neotropical liana, offers a unique system for studying gene flow across forest strata. Unlike most other plant species, M. longifolia produces flowers from the forest floor to the canopy, allowing us to study how bat pollination differs across strata. This study examines pollen dispersal distances, the vertical stratification of gene flow, and SGS in M. longifolia at a 100 ha study site in western Amazonia. Pollen dispersal distances were up to 1350 m, with longer distances observed in the understory and midstory, where bat foraging activity is more frequent. We detected no SGS, suggesting extensive gene flow facilitated by bat pollination across forest strata. These findings underscore the critical role of bats in shaping plant genetic structure and demonstrate how vertical forest stratification influences gene flow in tropical ecosystems.